The Effect of Spiritual Motivation and Compensation on The Employee Performance of The Bank of Center Sharia Jabar Banten - Laili Rahmawati (Review of Islamic Economics and Finance (RIEF), 2020)
Abstract.     Nowadays, the sharia banking industries in Indonesia have increased dramatically because many conventional banking companies have redeveloped to be sharia banking. According to many, the industries of sharia banking require the systems that can spur them to be a large banking company not only in Indonesia but also in the world. Meanwhile, the sources that they have both human and natural resources, respectively, need to compete in this era. Moreover, enhancing the capacity of employees is indispensable work to create great employees, which is essential for the sharia banking companies. This study aims to describe the impact of spiritual motivation and compensation on employee performance. The methodology used in this research is a survey method with explanatory likewise the spiritual motivation and the compensation are independent variables while employee performance is the dependent variable. In addition, the location of the survey is in the Bank of Center Sharia Jabar Banten. The result of the study has delivered that both the spiritual motivation and the compensation have a significant positive impact to incline the employee performance of the Bank of Center Sharia Jabar Banten. Keywords.    Sharia Banking, Spiritual Motivation, Compensation, and Employee Performance.